THU0524 Antidepressant use among Persons with Recent-Onset Rheumatoid Arthritis: A Nationwide Register-Based Study in Finland. (23rd January 2014) - Lönnroos, E.; Jyrkkä, J.; Kautiainen, H.; Koponen, H.; Virta, L. J.; Pohjolainen, T.; Puolakka, K.
Abstract : Background: Depression is a sizeable problem in rheumatoid arthritis (RA) but data on the antidepressant use is sparse. Objectives: To investigate antidepressant initiations and the prevalence of antidepressant use among persons with recent-onset RA. Methods: Persons (age ≥50) with incident RA (n=10356) during the years 2000-2007 were identified and data on their antidepressant purchases and comorbid conditions were obtained from the National Registers of Social Insurance Institution of Finland. Participants were categorized as former (antidepressant purchase during the year preceding RA diagnosis), new (first purchase after RA diagnosis) or non-users (no purchases during the study period) of antidepressants. Results: Ten percent of participants (n=1034) were former users of antidepressants, and 9.4% (n=975) initiated the use after RA diagnosis. Cumulative incidence of antidepressant initiations among men was 4.8% (95% CI: 4.1 to 5.6) at two years after RA diagnosis and 11.4% (95% CI: 10.0 to 12.9) at the end of follow-up (mean: 4.4 years). For women, corresponding incidences were 7.1% (95% CI: 6.5 to 7.8) and 16.2% (95% CI: 14.9 to 17.5). Rate of antidepressant initiations was higher in women [HR 1.39 (95% CI: 1.21 to 1.60)]. The number of comorbidities before RA was linearly associated with antidepressant initiations (p<0.001). The prevalence of antidepressant use among study participants was 11.3% (95% CI: 10.6 to 12.0) in the last follow-up year. Conclusions: Antidepressant initiations were relatively frequent after RA diagnosis and significantly associated with comorbidity burden. This warrants the importance of psychological evaluation in early RA, especially among persons with several comorbidities. Disclosure of Interest: None Declared